Lion’s Roar in SEA: Singaporean Way in Increasing the Awareness of Cybersecurity - Aufar Rizki (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2019)
Nowadays, where almost all aspect are digitilized have caused a massive increase of cyber threats which is a tangible threats for human beings. However, cybersecurity still has a second priority to accomplish for mostly countries, just few country who put big concern to this issue. As the Chair of ASEAN 2018, Singapore has made a project in strengthening the collective resillience of cybersecurity. The goal of this project is to increase the awareness of ASEAN countries in tackling cyberthreats in which it endangers the cybersecurity